COMPARATIVE ANALYSIS OF BIOGAS GENERATION FOR THE SOLID WASTE SECTOR USING UNMANNED AERIAL VEHICLE WITH THE BRAZILIAN MODEL OF GREENHOUSE GAS EMISSIONS IN AREAS WITH NO OPERATIONAL HISTORY - Lopes, Gustavo Aiex; Mozer, Thiago Simonato; Carli, Ana Alice de (Boletim de Ciências Geodésicas, 2018)
The city of Volta Redonda, located in the state of Rio de Janeiro, has a controlled landfill of municipal solid waste (MSW) which was partially recovered in 2008. This disposal site has no data on the amount of waste volume landfilled. An Unmanned Aerial Vehicle (UAV) was used to capture images of the study area and through Geographic Information Systems (GIS) the biogas generation was determined. By overlaying the georeferenced images the contour lines were determined which enabled the creation of the 3D Digital Terrain Model (DTM) of the area with a resolution of 0.296349 m / pix. The DTM provided the determination of the volume of waste landfilled (535.755,79 m3) and the real surface area (36.770,96 m2) of the controlled landfill. These parameters allowed obtainment the maximum flow rate of methane generation of 16.539,82 m3 for 2007. The Brazilian model used to determination biogas generation in waste sector achieve a maximum flow rate of methane generation of 126.599,4 m3 for the year 2007. A significant difference between biogas generation in the two models was observed mainly due to the amount of waste determined in both models.